Evaluation of physico-static and dynamic elastic properties of Eucalyptus pellita in various thinning intensities - Mansoor, Noorsyazwani; Muhammad Roseley, Adlin Sabrina; Gandaseca, Seca; Salim, Sabiha; Dahali, Rasdianah; Lee, Seng Hua (Universiti Putra Malaysia Press, 2024)
Acoustic velocity (AV) offers a non-destructive means of reliably measuring wood properties, presenting a valuable alternative to the traditional method known for its destructiveness, costliness, and time consumption. This technique is widely used in the timber industry to predict the bending strength of standing trees and logs. Hence, a study was conducted to assess the dynamic and static elastic properties of Eucalyptus pellita in various thinning intensities using the AV technique and laboratory testing. The selected 11-year-old E. pellita wood was obtained from thinning trials in Sabah Softwood Berhad, Brumas, Sabah. This investigation collected samples from three distinct thinning intensities (0%, 40%, and 60%). Dynamic modulus of elasticity (MOE), which relies on the time of flight (TOF) principle, was measured using an acoustic velocity approach, and physical and static testing was conducted according to standard ISO 13061. Results from this study show that thinning treatments significantly affect the physical and mechanical properties of E.pellita. The study also found that the static modulus of elasticity (MOE) value may be predicted using the acoustic velocity approach, with R2 = 0.46, R2 = 0.60, and R2 = 0.53 on standing trees, billets, and wood slabs, respectively. The application of non-destructive tests in forest plantations can help the foresters assess the wood properties efficiently, and specific parameters can be measured on a tree stand without falling the tree. Besides, thinning at a moderate intensity also helped to enhance the mechanical properties and dynamic MOE value of the E. pellita wood.